The fight against corruption in Brazil: a case of good governance? - Pohlmann, Markus; Valarini, Elizângela (Knowledge for governance, 2020)
The “Operation Carwash” is so far the biggest corruption scandal in Brazilian history. It did spoil a major part of the political system, and some of the established governance practices in Brazil. In this article, we are taking a closer look into the big corruption case, analyzing the unlawful practices of the Brazilian construction companies, and their relationship with the public sector more thoroughly. By carrying out content analyses of court files, we reveal the systemic corrupt pattern behind by connecting the level of regulations with the level of organizational crime. Furthermore, we ask, if the recent changes in law enforcement are accompanied by a changing environment of good governance? Our answer presented in the second part of the article is no. The political reactions to the “operation carwash” revealed in fact, how many of the “old-school” governance practices survived in Brazil.
Gesehen am 05.12.2022